Use of virtual reality in oncology: From the state of the art to an integrative model - Buche, Hélène; Michel, Aude; Blanc, Nathalie (Frontiers in Virtual Reality, 2022)
Over the past twenty years, virtual reality (VR) has been the subject of growing interest in oncology. More and more researchers are studying the effects of virtual environments to contribute to current thinking on technologies likely to support patients undergoing oncological treatment. Recent research highlights how VR can divert attention while reducing anxiety in stressful healthcare situations through its multisensory and participative nature. VR appears to be a promising tool capable of reducing cancer-related anxiety symptoms, improving treatment adherence, and increasing satisfaction with oncology care. While the literature reports these positive effects in the therapeutic management of cancer, few studies have focused on theoretical models capable of explaining the psychological benefits of virtual immersion. This literature review provides a theoretical framework combining results from all relevant empirical work in oncology. The review can help researchers identify the optimal conditions for using VR in oncology and bridge the gap between divergent devices, modalities, and practices (e.g., headmounted displays, environments, interactivity, immersion time).